2022
DOI: 10.1002/jmv.28259
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of IFIT3 in antiviral innate immunity and cellular biology

Abstract: The interferon‐inducible protein with tetrapeptide repeats 3 (IFIT3) is one of the most important members in both the IFIT family and interferon‐stimulated genes family. IFIT3 has typical features of the IFIT family in terms of gene and protein structures, and is able to be activated through the classical PRRs‐IFN‐JAK/STAT pathway. A variety of viruses can induce the expression of IFIT3, which in turn inhibits the replication of viruses, with the underlying mechanism showing its crucial role in antiviral innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…These data indicate that over a wide range of IFN doses, ZAP, IFIT3, and IFIT1 together comprise an outsized proportion of the total IFN-mediated suppression of VEEV-GFP. ZAP, IFIT3, and IFIT1 have been shown to exhibit broad antiviral activity towards diverse viruses (Andrejeva et al, 2013;Bick et al, 2003;Chikhalya et al, 2021;Fensterl & Sen, 2015;Gao et al, 2002;Gonzalez-Perez et al, 2021;Griffante et al, 2021;Hyde et al, 2014;Johnson et al, 2018;Pichlmair et al, 2011;Reynaud et al, 2015;Schmeisser et al, 2010;Zhang et al, 2022). We therefore used gene silencing to determine the contribution of ZAP, IFIT3, and IFIT1 to the antiviral activity of IFN towards other IFN-sensitive viruses.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that over a wide range of IFN doses, ZAP, IFIT3, and IFIT1 together comprise an outsized proportion of the total IFN-mediated suppression of VEEV-GFP. ZAP, IFIT3, and IFIT1 have been shown to exhibit broad antiviral activity towards diverse viruses (Andrejeva et al, 2013;Bick et al, 2003;Chikhalya et al, 2021;Fensterl & Sen, 2015;Gao et al, 2002;Gonzalez-Perez et al, 2021;Griffante et al, 2021;Hyde et al, 2014;Johnson et al, 2018;Pichlmair et al, 2011;Reynaud et al, 2015;Schmeisser et al, 2010;Zhang et al, 2022). We therefore used gene silencing to determine the contribution of ZAP, IFIT3, and IFIT1 to the antiviral activity of IFN towards other IFN-sensitive viruses.…”
Section: Resultsmentioning
confidence: 99%
“…IFNB1 and other type I interferons activate the JAK-STAT cascade that induces interferon-stimulated genes such as IFIT2 (also called ISG54), IFIT3 (ISG60), and ISG15. IFIT2 (selected in C) and IFIT3 (selected in R) encode cytoplasmic proteins that restrict replication of corona-and many other viruses by sensing viral mRNAs and inhibiting their translation [76][77][78][79] . ISG15 is an antiviral protein that lacks a key Cysteine residue in rhinolophid and hipposiderid bats which is required for homodimer formation (investigated in detail below).…”
Section: Relevant Immune-related Changes In Batsmentioning
confidence: 99%
“…Regarding the known role of IFIT3 in antiviral innate immunity, 20 to further investigate the mechanism of IFIT3 in inhibiting EBV lytic replication, we examined the effect of IFIT3 on a subset of ISGs.…”
Section: Ifit3 Increases the Transcription Of Isgs In Ebv Lytic Repli...mentioning
confidence: 99%
“…18,19 The IFN-induced protein with tetratricopeptide repeats 3 (IFIT3) is a member of the IFIT family and one of the important ISGs. 20 Without external stimuli, most cells do not express or poorly express IFIT3. A mountain of studies has shown that a variety of RNA or DNA viruses can induce the expression of IFIT3, including rabies virus (RV), 21 BK polyomavirus, 22 hepatitis C virus (HCV) 23,24 and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 99%